Early ERP Evidence for Children’s and Adult’s Sensitivity to Scalar Implicatures Triggered by Existential Quantifiers (Some) - Panizza, Daniele; Onea, Edgar; Mani, Nivedita (Frontiers in Psychology, 2021)
How quickly do children and adults interpret scalar lexical items in speech processing? The current study examined interpretation of the scalar terms some vs. all in contexts where either the stronger (some = not all) or the weaker interpretation was permissible (some allows all). Children and adults showed increased negative deflections in brain activity following the word some in some-infelicitous versus some-felicitous contexts. This effect was found as early as 100ms across central electrode sites (in children), and 300-500ms across left frontal, fronto-central and centro-parietal electrode sites (in children and adults). In contrast, participants showed increased positive deflections in brain activity across the centro-parietal region (children) and left frontal and posterior regions (adults) to the word all in some-felicitous relative to infelicitous pictorial contexts. Again, this effect was earlier in children relative to adults. Given the diametrically different ERPs to some vs. all in matching and mismatching visual contexts, our results strongly suggest that young children (aged between three to four years) as well as adults quickly have access to the contextually appropriate interpretation of scalar terms.